Pemanfaatan Teknologi Informasi dan Komunikasi (Tik) Dalam Peningkatan Mutu Layanan Manajemen Sekolah di SDN Selanglet - Vega Novia Asrila Husni; I Gede Yudana; Mohamad Mustari; Syarifuddin Syarifuddin (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2025)
This study aims to explore in depth how the application of Information and Communication Technology (ICT) can encourage the improvement of the quality of managerial services at SDN Selanglet. In the context of education modernization, ICT is expected not only to be a learning tool, but also an important pillar in supporting a more effective, efficient and transparent school governance system. Using a qualitative approach and case study design, this research collected data through in-depth interviews, direct field observations, and analysis of internal school documents. The findings of this study show that the utilization of ICT plays a significant role in accelerating administrative processes, simplifying reporting mechanisms, and improving the quality of communication between the school, students, parents and other stakeholders. The implementation of ICT at SDN Selanglet is carried out in stages, starting from the initial strategy of providing basic equipment and digital literacy training for educators and education personnel, to the advanced strategy of developing a digital-based school information system. The key to the success of this digital adaptation lies in the harmonious collaboration between principals, teachers and administrative staff who demonstrate a high commitment to technology-based management innovation. Overall, the results of this study emphasize that the existence of ICT is not only a technical tool, but also a tool that can be used to support the school.